Learning Obstacles of Prospective Mathematics Teachers: a Case Study on the Topic of Implicit Derivatives - Entit Puspita; Didi Suryadi; Rizky Rosjanuardi (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
This research is a Didactical Design Research (DDR), aiming to identify various learning barriers for prospective mathematics teachers. Some students still experience learning difficulties in derived concepts which are prerequisites for other concepts or other subjects, didactic and pedagogical anticipation can be prepared to overcome them. Based on the learning design, various learning barriers were identified, especially in the implicit derivative concept. The research participants consisted of 3 lecturers and 46 second-semester prospective teacher students at one of the tertiary institutions in Indonesia. The results of interviews and questionnaires were analyzed through identification, clarification, reduction and verification techniques and then presented narratively. The results showed that some prospective teachers experienced learning barriers 1) ontogenic instrumental, conceptual, and psychological types, 2) didactic, students could not identify contextual relationships in the structure of answers, indicating that the material was not by the continuity of students' thinking, and 3) epistemological, the lack of understanding of explicit and implicit similarities shows the limitations of the context that students have. Based on the research findings, a learning design will be developed based on the theory of a didactic situation with the stages of action situations, formulation, validation, and institutionalization, which are thought to be able to overcome the findings of learning obstacles.Penelitian ini merupakan Didactical Design Research (DDR), bertujuan untuk mengidentifikasi berbagai hambatan belajar calon guru matematika. Sebagian mahasiswa masih mengalami hambatan belajar pada konsep turunan yang merupakan prasyarat konsep lain atau matakuliah lain, dapat disiapkan antisipasi didaktis maupun pedagogis untuk mengatasinya. Berdasarkan rancangan pembelajaran, diidentifikasi berbagai hambatan belajar khususnya pada konsep turunan implisit. Partisipan penelitian terdiri dari 3 dosen dan 46 mahasiswa calon guru semester dua di salah satu perguruan tinggi di Indonesia. Hasil wawancara dan angket dianalisis melalui teknik identifikasi, klarifikasi, reduksi, dan verifikasi, selanjutnya disajikan secara naratif. Hasil penelitian menunjukkan bahwa beberapa calon guru mengalami hambatan belajar 1) ontogenik tipe instrumental, konseptual, dan psikologis, 2) didaktis, mahasiswa tidak dapat mengidentifikasi hubungan kontekstual dalam struktur jawaban, menunjukkan bahwa materi tidak sesuai dengan kesinambungan proses berpikir mahasiswa, dan 3) epistemologis, kurangnya pemahaman persamaan eksplisit dan implisit menunjukkan keterbatasan konteks yang dimiliki mahasiswa. Berdasarkan temuan penelitian, akan dikembangkan desain pembelajaran berdasarkan theory of didactical situation dengan tahapan situasi aksi, formulasi, validasi, dan institusionalisasi yang diduga dapat mengatasi temuan hambatan belajar.